SPP1+macrophages promote fibroblast-to-myofibroblast transformation during hypoxia in deep fascia of acute compartment syndrome - Zheng, Liujie; Li, Guoqiang; Cao, Jingcheng; Zhao, Zihang; Wang, Haofei; Dong, Qi; Hou, Zhiyong (Frontiers in Immunology, 2025)
BackgroundAcute compartment syndrome (ACS) is a life-threatening condition characterized by elevated intracompartmental pressure leading to ischemia, hypoxia and tissue necrosis. We have observed an increase in SPP1+macrophages and fibroblast activation in the deep fascia of ACS patients. However, the mechanisms underlying the pathological changes in terms of macrophage activation and fibroblast responses remain poorly understood.ObjectivesThis study aims to investigate whether hypoxia induces SPP1+ macrophages in the deep fascia of ACS, and to elucidate how these macrophages contribute to fibroblast activation and myofibroblast transformation.MethodsMacrophages were cultured under normoxic and hypoxic conditions, with or without SPP1 siRNA transfection. The concentration of SPP1 in the macrophage-conditioned media was determined using an ELISA assay. The culture supernatant from each condition was then applied to fibroblasts, which were subsequently analyzed for mRNA and protein expression of fibroblast activation markers by qRT-PCR and WB, respectively.ResultsHypoxia significantly upregulated SPP1 expression in macrophages, as well as in the macrophage-conditioned media. Moreover, hypoxia-stimulated macrophages promoted fibroblast expression of ACTA2, CTGF, collagen I, collagen III, and FN1 at both mRNA and protein levels. This effect was reversed by SPP1 siRNA transfection.ConclusionsHypoxia induces SPP1+macrophages, which in turn activate fibroblasts, driving myofibroblast transformation in ACS. Targeting this pathway may provide a potential therapeutic strategy for mitigating fibrosis and improving outcomes in ACS.